Efek Formalin terhadap Jumlah Sel Spermatogenik - Dhalila, Hasyifa; Zulfitri, Zulfitri; Sofia, Sofia (Universitas Ahmad Dahlan, 2017)
Background: The high number of formalin abuse as a food additive and formaldehyde exposure in daily life can caused the adverse effect, one of that is infertility. The purpose of this research was to determine the effect of formaldehyde on the number of spermatogenic cells, which illustrated disruption of spermatogenesis. Methods: This research was an experimental research with post-test only with control group design. The subject of this research were 24 white rats (Rattus norvegicus) Wistar strain. Test of Hiypothesis used software of Statistical Package for the Social Sciences (SPSS) with One-way Anova test with significance 0.05. Results: The average number of spermatogonia cells (P0:291.50; P1:237.50; P2:185.83; P3:156.67), primary spermatocytes cells (P0:296,17; P1:261,33; P2:203,83; P3:171,33), and spermatid cells (P0:722.67; P1:663.67; P2:385.00; P3:287.83) decreased than control, and the results of One-way Anova test was p=0.00. Conclusion: There was a significant difference in the number of spermatogenic cells of the control group with the formalin treatment group.